El cálculo del interés a cargo del sujeto activo por un cobro en exceso o indebido, desde la fecha en que se presentó la respectiva solicitud o reclamo; y no desde la fecha en que se originó; genera un perjuicio económico y vulneración de los derechos fundamentales del contribuyente - Mazza Gómez, Anna Karina (2015)
In the Ecuadorian tax administration is common for the improper payment or overpayment by the active subject of tax liability occurs, that usually follows taxpayer errors or responsible, or situations from the tax administration itself. When recurrent situation is important that it be regulated efficiently in the Tax Code , but in reviewing the relevant rules was established that the regulation of interest over the assets subject, concept of undue payment or overpayment, suffers from a problem that affects the constitutional principles of equality and fairness in taxation, when the article twenty of the Code determines that the interest calculation will be from the date on which the taxpayer submits the application or claim, and not from when it became the respective payment. This discriminatory situation affects the economic interests and fundamental rights of taxpayers, so it is studied in this paper titled: "THE CALCULATION OF INTEREST BY THE ACTIVE SUBJECT FOR A RECOVERY IN EXCESS OR ABUSE FROM THE DATE THAT WAS FILED IN THE RESPECTIVE APPLICATION OR CLAIM; AND NOT FROM THE DATE ON WHICH ORIGINATED; CREATES ECONOMIC INJURY AND VIOLATION OF FUNDAMENTAL RIGHTS OF THE TAXPAYE" research is based on a theoretical basis where conceptual doctrinal and legal opinions are presented, and results based on a field research process, all of which leads to the conclusion that there is a need to reform the tax code Ecuador to ensure more effectively the rights of taxpayers, and ensure the exercise of a more efficient and fair tax administration.